Opportunities and Challenges of the Global Market for MSMEs - Seto Indarto; Muhammad Maulana Iskhak (Cita konsultindo, 2025)
This research uses the literature review method. The purpose of this research is to identify the opportunities and challenges faced by Indonesian MSMEs in the global market, particularly in the era of Society 5.0. The results of this study show that the contribution of Indonesian MSMEs is minimal due to the many challenges they face, such as (1) low productivity of MSMEs, indicated by the tendency for MSMEs to act as sales partners, (2) high import volumes leading to the emergence of predatory pricing practices, (3) limited physical and non-physical infrastructure, (4) limited access to business financing and legality, and (5) the limited capacity of human resources in Indonesia. Despite these challenges, in the era of Society 5.0, Indonesian MSMEs also have great opportunities, marked by the emergence of the digital ecosystem concept (e-commerce) and broader global market opportunities due to the liberalization of international trade. Therefore, it is hoped that with these significant opportunities, Indonesian MSMEs will continue to thrive in the global market and contribute positively in terms of employment and national economic growth.